Prototipe Living Qur’an Pendidikan Dasar di Madrasah Ibtidaiyah: Studi Kasus di MI Nurul Ummah Kotagede Yogyakarta - Assingkily, Muhammad Shaleh; Baroroh, R. Umi (JOIES (Journal of Islamic Education Studies), 2017)
This article aims to study the learning activities of the tah}fi>z} and tah}si>n programs that are implemented at Nurul Ummah Islamic School. The formulation of the problem in this study is how the efforts of the madrasah in living Qur’an at MI Nurul Ummah and how the role of the tah}fi>z} and tah}si>n al-Qur'an programs in fostering the love of the Qur'an for students of MI Nurul Ummah. The research used a qualitative approach with the setting of activities, namely the application of the tah}fi>z} and the tah}si>n al- Qur'an programs at MI Nurul Ummah. The results of this research indicate that the efforts of living quran have been carried out at MI Nurul Ummah this can be seen from the madrasah’s routine, supervision activities, adequate time allocation, qualified educators, and intense communication with parents of students, Likewise, the tah}fi>z} and tah}si>n programs an important role in fostering the love of children for the Qur'an as seen from the quantity aspect in the form of increasing student memorization and quality aspects in the form of reading students according to the rules of tajweed (and makharijul huruf) and practicing worship (obligatory and sunnah).